Malpraktik Medik dan Pertanggungjawaban Hukumnya: Analisis dan Evaluasi Konseptual - Muh Endriyo Susila (Universitas Muhammadiyah Surakarta, 2021)
Although medical malpractice is not really new phenomenon in Indonesia, nevertheless dealing with medical malpractice cases is confusing to some extent. The absence of statutory definition of medical malpractice leads to confusion on how to handle it. This paper aims at elaborating the concept of medical malpractice and its liability. In addition, misconception on medical malpractice liability will also be evaluated. This normative legal research relies on secondary data and employes both statutory and comparative approaches. It is found that there has been misconception on medical malpractice in Indonesia. The misconception takes place not only to the lay persons, but also among academicians and law enforcement agencies. This misconception has led to confusion on how to establish medical malpractice liability.